Physicochemical and Sensory Characteristics of Flakes made of Proportion of Breadfruit Flour (Artocarpus altilis) and Mocaf (Modified Cassava Flour) and Concentration of Sodium Bicarbonate - Kurniasari, Novia Indah; Rosida, Dedin Finatsiyatull; Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Flakes are a thin, sheet-shaped food with a brownish-yellow color and are usually consumed with milk as a breakfast menu. In this research, we will make flakes using a combination of breadfruit flour and Mocaf flour. The purpose of this research was to determine the effect of the proportion of breadfruit flour and mocaf flour and the concentration of sodium bicarbonate on the physicochemical and organoleptic characteristics of the quality of the flakes produced. This research used a completely randomized design (CRD) factorial pattern with two factors and two replications. Factor I is the proportion of breadfruit flour and mocaf flour consisting of 10:90, 20:80, and 30:70. Factor II is the concentration of sodium bicarbonate, namely 0.3%, 0.4%, and 0.5%. If there is a significant difference, it will be continued with the DMRT 5% further test. The best treatment results were obtained in the treatment of the proportion of breadfruit flour (20%) and mocaf flour (80%) and sodium bicarbonate concentration of 0.4%, namely water content 3.48%, ash content 2.63%, fat content 1.67%, protein content 3.81%, carbohydrate content 87.22%, starch content 78.58%, rehydration power 125.32% and organoleptic values, which include color 3.72 (Slightly brownish yellow), aroma 3.48 (Slightly languorous), taste 3.92 (Slightly savory), and crunchiness 3.92 (slightly crunchy). Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-BeingSDG 9: Industry, Innovation, and InfrastructureSDG 13: Climate Action